PUBLIC AWARENESS AND PRACTICE REGARDING PREMARITAL SCREENING FOR SICKLE CELL DISEASE, IN AL-BAHA REGION: A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
BackgroundSickle cell disease (SCD) is a hereditary blood disease that is prevalent in Saudi Arabia, especially in eastern and southwest regions, such as Al-Baha region. Premarital screening may be an effective practical way to decrease SCD prevalence and incidence in the future generations. The current study explores the frequency of premarital screening in Al-Baha region and investigated causes and barriers of not performing premarital screening.Methods This is a cross-sectional study conducted over a period of three months, from December 17, 2023, to March 17, 2024, among the general population of Saudi Arabia's Al-Baha region. An online questionnaire was used for data collection. Data included sociodemographic data, medical and family history of SCD, awareness, perception, and prevalence of undergoing premarital screening for SCD, and barriers for undergoing premarital screening for SCD.ResultsThe study included 478 participants with age ranged between 18 and 60 years. Around 63.4% of the participants were females. Around 334 (69.9%) were married or engaged, and of whom 221 (66.2%) had consanguinity. The study showed that among the participants who were married or engaged, only 167 (50%) underwent premarital screening. The sickle cell trait was reported in 75 (15.7%), while SCD was reported by 54 (11.3%). Only 301 (63.0%) heard of premarital screening and 286 (59.8%) heard of SCD.ConclusionPremarital screening in Al-Baha region is unsatisfactory compared to other parts of the country. This can be attributed to the low level of awareness and knowledge regarding premarital screening program and SCD among the general population of Al-Baha.